AKIBAT HUKUM PUTUSAN MK NO. 97/PUU-XIV/2016 TENTANG JUDICIAL REVIEW UU ADMINISTRASI KEPENDUDUKAN TERHADAP PENGHAYAT ALIRAN KEPERCAYAAN - Shandy Harsyahwardhana (Arena Hukum, 2020)
AbstractCarrying out the mandate of the 1945 Constitution which guarantees the right to freedom of religion and belief, the Constitutional Court issued Decision Number 97/ PUU-XIV / 2016 which granted the judicial review lawsuit on Law 23 of 2005 jo. Law 24 of 2013 concerning Population Administration. The Constitutional Court ruled that Article 61 paragraph (1), (2) and Article 64 paragraph (1), (2) of the Population Admnistration Law contradicts the 1945 Constitution of the Republic of Indonesia. This paper aims to identify and analyze the Constitutional Court's considerations in issuing the decision, and the legal consequences of that ruling. This normative legal research uses a case approach. The results found that the decision of the Constitutional Court had a significant legal effect on the followers of the flow of trust and had implications that impact not only in terms of the law but also sub-systems in pluralistic Indonesian society.Â Abstrak Melaksanakan amanat UUD 1945 yang menjamin hak kebebasan beragama dan berkeyakinan, Mahkamah Konstitusi mengeluarkan Putusan Nomor 97/PUU-XIV/2016 yang mengabulkan gugatan judicial review atas UU 23 Tahun 2005 jo. UU 24 Tahun 2013 tentang Administrasi Kependudukan. Mahkamah Konstitusi memutuskan bahwa Pasal 61 ayat (1), (2) dan Pasal 64 ayat (1), (2) UU Adminduk bertentangan dengan UUD NRI Tahun 1945. Tulisan ini bertujuan untuk mengetahui dan menganalisis pertimbangan Mahkamah Konstitusi dalam mengeluarkan putusan tersebut, serta akibat hukum dari putusan itu. Penelitian hukum normatif menggunakan pendekatan kasus (case approach). Â Hasilnya ditemukan bahwa putusan Mahkamah Konstitusi memiliki akibat hukum yang signifikan pada penghayat aliran kepercayaan serta memiliki implikasi yang berdampak tidak hanya dari segi hukum namun juga sub-sistem di masyarakat Indonesia yang pluralistik.